A Novel Multidisciplinary Intervention for Long-Term Weight Loss and Glycaemic Control in Obese Patients with Diabetes - Anna Lih; Lorraine Pereira; Ramy H. Bishay; Johnson Zang; Abdullah Omari; Evan Atlantis; Nic Kormas (Journal of Diabetes Research)
Introduction. Obesity and diabetes are difficult to treat in public clinics. We sought to determine the effectiveness of the Metabolic Rehabilitation Program (MRP) in achieving long-term weight loss and improving glycaemic control versus “best practice” diabetes clinic (DC) in obese patients using a retrospective cohort study. Methods. Patients with diabetes and BMI > 30 kg/m2 who attended the MRP, which consisted of supervised exercise and intense allied health integration, or the DC were selected. Primary outcomes were improvements in weight and glycaemia with secondary outcomes of improvements in blood pressure and lipid profile at 12 and 30 months. Results. Baseline characteristics of both cohorts (40 MRP and 40 DC patients) were similar at baseline other than age (63 in MRP versus 68 years in DC, P=0.002). At 12 months, MRP patients lost 7.65 ± 1.74 kg versus 1.76 ± 2.60 kg in the DC group (P<0.0001) and 9.70 ± 2.13 kg versus 0.98 ± 2.65 kg at 30 months (P<0.0001). Similarly, MRP patients had significant absolute reductions in %HbA1c at 30 months versus the DC group (−0.86 ± 0.31% versus 0.12% ± 0.33%, P<0.038), with nonsignificant improvements in lipids and blood pressure in MRP patients. Conclusion. Further research is needed to establish the MRP as an effective strategy for achieving sustained weight loss and improving glycaemic control in obese patients with type 2 diabetes.